NEAR-RING PRIMA DAN SEMIPRIMA YANG DILENGKAPI DENGAN DERIVATIF - Ningrum Astriawati (Jurnal Edukasi dan Sains Matematika (JES-MAT), 2015)
Let be a semiprime near-ring with derivations of . Derivations are referred to group additive endomorphism with multiplication operating of (. )= ()+ () = 0  for each , . This paper gives sufficient conditions on a subset near-ring order derivation of each of its members is equal to 0. Let N be a semiprime near-ring and AÍN such that 0 ,. and d derivation of N. The purpose of this paper is to prove that if d acts as a homomorphism on A or as an anti-homomorphism on then d(A) = 0